17.4k views
0 votes
What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.

x = StartFraction negative 3 plus-or-minus 3 i StartRoot 3 EndRoot Over 2 EndFraction
x = StartFraction 7 plus-or-minus 3 i StartRoot 3 EndRoot Over 2 EndFraction
x = 2
x = 8

2 Answers

6 votes

Answer:

Option 2

Explanation:

I just took the test and got it right.

User Alexander Reznikov
by
4.8k points
1 vote

Answer:

Option 2 -
x=(7\pm3√(3)i)/(2)

Explanation:

Given : Equation
(x-5)^2+3(x-5)+9=0

To find : What is the solution of the equation ?

Solution :

Using substitution method,

Let y=x-5


y^2+3y+9=0

Using quadratic formula,
x=(-b\pm√(b^2-4ac))/(2a)

Here, a=1, b=3 and c=9


y=(-3\pm√(3^2-4(1)(9)))/(2(1))


y=(-3\pm√(-27))/(2)


y=(-3\pm3√(3)i)/(2)

Substitute back,


x=(-3\pm3√(3)i)/(2)+5


x=(-3\pm3√(3)i+10)/(2)


x=(7\pm3√(3)i)/(2)

Therefore, option 2 is correct.

User Konstantin Ershov
by
4.8k points